Implementasi Internet of Things pada Otomasi Pemberian Pakan Ayam Ras Petelur - Lukie Perdanasari; Bety Etikasari; Trismayanti Dwi Puspitasari; Ratih Ayuninghemi (Jurnal Teknologi Informasi dan Multimedia, 2024)
Adequate nutrition affects the quality and quantity of egg production which has an impact on the profitability of laying hen breeders. Rizqie Farms experienced problems with the management of feeding laying hens, when the rainy season and open cage conditions made feeding irregular. It is important to be disciplined in feeding layer chickens on time at the same time as a research ur-gency, so that the chickens do not become stressed so that discipline in feeding management increases the quality and quantity of egg production. The design thinking method as a meth-od-ology for completing the creation of Android smartphone tools and applications. The com-pletion stages start with empathize, define, ideate, prototype and test. The materials used to make the tool are ESP32 DEVKIT V1 S2, Ultrasonic Sensor, Servo driving droplet feed, Power Source/Supply 12v 1A, Stepper Motor Driver l928n, Stepper Motor Nema 17 20nm, DS3231 RTC Module (timer), Arduino Uno R3, Buzzer / Speaker, LCD 1062 16x2 with I2c port. Sensor data connected to the ESP32 DEVKIT V1 S2, Ultrasonic Sensor, Servo drive is converted to an Android smartphone as a monitoring medium. Monitoring is carried out via a mobile application, with the Internet of Things connected to the device as an internet-based communication medium. Feeding equipment testing had an average delay of 40.2 seconds and MSE 0,0514. Black box testing was carried out to test the functionality of the monitoring application on 5 users with a percentage of 100%.